Public hospital reform, family health consumption and health inequality: evidence from China Family Panel Studies - Jiang, Lan; He, Yiqing; Hu, Chunqi (Frontiers in Public Health, 2024)
Background In 2017, China launched a comprehensive reform of public hospitals and eliminated drug markups, aiming to solve the problem of expensive medical treatment and allow poor and low-income people to enjoy basic health opportunities. This study attempts to evaluate the policy impact of public hospital reform on the health inequality of Chinese residents and analyze its micro-level mechanism from the perspective of household consumption structure. Studying the inherent causal connection between public hospital reform and health inequality is of paramount significance for strengthening China’s healthcare policies, system design, raising the average health level of Chinese residents, and achieving the goal of ensuring a healthy life for individuals of all age groups. Methods Based on the five waves of data from the China Family Panel Studies (CFPS) conducted in 2012–2020, We incorporates macro-level statistical indicators such as the time of public hospital reforms, health insurance surplus, and aging, generating 121,447 unbalanced panel data covering 27 provinces in China for five periods. This data was used to explore the impact of public hospital reform on health inequality. Logical and empirical tests were conducted to determine whether the reform, by altering family medical care and healthy leisure consumption expenditures, affects the micro-pathways of health inequality improvement. We constructed a two-way fixed model based on the re-centralized influence function (RIF_CI_OLS) and a chained mediation effects model to verify the hypotheses mentioned above. Results Public hospital reform can effectively improve the health inequality situation among Chinese residents. The reform significantly reduces household medical expenses, increases healthy leisure consumption, promotes the upgrading of family health consumption structure, and lowers the health inequality index. In terms of indirect effects, the contribution of the increase in healthy leisure consumption is relatively greater. Conclusion Public hospital reform significantly alleviates health inequality in China, with household health consumption serving as an effective intermediary pathway in the aforementioned impact. In the dual context of global digitization and exacerbated population aging, enhancing higher education levels and vigorously developing the health industry may be two key factors contributing to this effect.